Field-Modulated Anomalous Hall Conductivity and Planar Hall Effect in Co3Sn2S2Nanoflakes - Yang, Shuo-Ying; Noky, Jonathan; Gayles, Jacob; Dejene, Fasil Kidane; Sun, Yan; Dorr, Mathias; Skourski, Yurii; Felser, Claudia; Ali, Mazhar Nawaz; Liu, Enke; Parkin, Stuart S. P. (Nano Letters, 2020)
Time-reversal-symmetry-breaking Weyl semimetals (WSMs) have attracted great attention recently because of the interplay between intrinsic magnetism and topologically nontrivial electrons. Here, we present anomalous Hall and planar Hall effect studies on Co3Sn2S2nanoflakes, a magnetic WSM hosting stacked Kagome lattice. The reduced thickness modifies the magnetic properties of the nanoflake, resulting in a 15-Time larger coercive field compared with the bulk, and correspondingly modifies the transport properties. A 22% enhancement of the intrinsic anomalous Hall conductivity (AHC), as compared to bulk material, was observed. A magnetic field-modulated AHC, which may be related to the changing Weyl point separation with magnetic field, was also found. Furthermore, we showed that the PHE in a hard magnetic WSM is a complex interplay between ferromagnetism, orbital magnetoresistance, and chiral anomaly. Our findings pave the way for a further understanding of exotic transport features in the burgeoning field of magnetic topological phases.
CRIS-Team Scopus Importer:2022-04-14
Keywords: anomalous Hall effect; Berry curvature; magnetic Weyl semimetal; planar Hall effect